Resolvable discrepqncies in the new Criminal Procedure Code (Academic Journal of Internal Affairs, 2019)
One of the important control efforts of the new law on criminal procedure is that, to speed up procedures, the opportunities of rendering inoperative should be straightened at revisions of judge decisions. The study intends to present principal bases of the codification attempts with scientific pretentio
Keywords: Criminal Procedure; resolvable discrepqncies; repeal